How to Build an Institution. Issue 2 (March 2021) - van Basshuysen, Philippe
How should institutions be designed that "work" in bringing about desirable social outcomes? I study a case of successful institutional design—the redesign of the National Resident Matching Program—and argue that economists assume three roles when designing an institution, each of which complements the other two: first, the designer combines positive and normative modeling to formalize policy goals and to design possible mechanisms for bringing them about. Second, the engineer refines the design by conducting experiments and computational analyses. Third, the plumber implements the design in the real world and mends it as needed.